Analysis of Factors Affecting Entrepreneurial Interest in Economics Education Study Program Students - Margareta, Elisabeth; Sitinjak, Erni Kusrini (Budapest International Research and Critics University, 2021)
This research was conducted to properly educate and prepare college graduates for entrepreneurship because many university graduates have become unemployed coupled with the Covid-19 pandemic since the beginning of 2020. The purpose of this research is to see how much income, family environment, and education affect students' interest in entrepreneurship. Economic Education in order to be able to develop an entrepreneurial spirit in students. This type of research is associative research which aims to determine the effect of independent variables (income, family environment, and education) on the dependent variable (interest in entrepreneurship) by using purposive random sampling technique. Based on the research conducted, it was found that income affects the entrepreneurial interest of students of the Economic Education study program by 79.6%, the family environment affects the entrepreneurial interest of students of the Economic Education study program by 62.5%, education affects the entrepreneurial interest of students of the Economics Education study program by 77, 9%. Furthermore, income, family environment, and education simultaneously or together have a positive and significant effect on the entrepreneurial interest of students of the Economic Education study program by 82.2%.